TECTONO-METAMORPHIC HISTORY OF THE DUARTE TERRANE (JARABACOA AREA, HISPANIOLA ISLAND): INSIGHTS ON THE TECTONIC EVOLUTION OF THE NORTHERN RIM OF THE CARIBBEAN OCEANIC PLATEAU - Marroni, Michele; Pandolfi, Luca; Giunta, Giuseppe; Malasoma, Alessandro (Ofioliti, 2008)
The northern margin of the Caribbean Plate is characterized by a transpressional belt consisting of an assemblage of several terranes derived from Late Cretaceous to Tertiary oblique convergence between the Northern American and Caribbean Plates. Fragments of the oceanic plateau belonging to the Caribbean Plate are incorporated in these belts as strongly deformed and metamorphosed sequences, as recognized in the Jarabacoa area of the Hispaniola Island. In this area the Duarte Terrane consists of two different units showing different metamorphic grades. The lower unit consists of greenschist facies metabasites, whereas the upper one is represented by amphibolite facies metabasites topped by metasedimentary rocks, whose protoliths were clastic deposits supplied by a magmatic arc. Both units suffered four deformation phases, from D1 to D4, that can be strictly correlated. In both units the D1 phase is characterized by a syn-metamorphic foliation associated to a mineral lineation and very rare rootless isoclinal folds. The D2 phase is characterized by a well developed foliation and isoclinal folds acquired under retrograde metamorphic conditions. The D1 and D2 phases developed in the Cenomanian-Turonian time span. The following D3 and D4 phases produced weak deformations without metamorphic imprint. The D3 and D4 phase are probably connected with transpression tectonics of Early Oligocene to Early Miocene age. All these deformations developed in an arc setting connected with southward oblique subduction of the oceanic lithosphere of the North America Plate beneath the Caribbean oceanic plateau.